Newcomers' Trait Positive Affectivity and Social Assimilation in Organizations: Testing the Mediating Role of Proactive Relationship Building Behaviors. (May 2019) - Li, Hairong; Fan, Jinyan; Yao, Xiang; Zheng, Lu
Becoming assimilated into the social environment at an organization is critical and challenging to newcomers. The present study examined whether newcomers' trait positive affectivity (PA) could predict social assimilation through proactive relationship building behaviors including general socializing, relationship building with boss, and networking. Participants in this three-wave survey study were 323 new employees in three organizations in China. Results based on structural equation modeling showed that newcomers' trait PA at T1 (within 2 weeks postentry) was positively related to all three dimensions of relationship building behaviors at T2 (8 weeks postentry); however, only general socialization was found to mediate the relationships between PA and two social assimilation outcomes at T3 (14 weeks postentry), that is, social integration and affective organizational commitment. Theoretical and practical implications were discussed.